Reframing 'well-being' in schools: the potential of recognition. Issue 4 (2nd October 2017) - Graham, Anne; Powell, Mary Ann; Thomas, Nigel; Anderson, Donnah
Abstract: In Australia and internationally, the well-being of children and young people is a core focus of social policy, with a growing imperative to locate well-being within the sphere of education. However, the term 'well-being' remains ambiguous and the implementation of educational approaches to promote and improve it appears fragmented and ad hoc. In Australia, little is known about how well-being is understood and supported in schools, particularly from the perspective of students themselves. This article reports on key findings from an ambitious mixed-methods study funded by the Australian Research Council that investigated conceptualisations and practices around well-being in schools. Underpinned by theoretical interests linked to Childhood Studies and recognition theory, the research investigated policy, student and staff perspectives on well-being. The findings point to the key role of relationships, providing considerable scope for analysing the salience of Honneth's modes of recognition for well-being in schools.